All-star 3 workbook - Lee, Linda; Sherman, Kristin; Sloan, Stephen; Tanaka, Grace; Velasco, Shirley (New York McGraw-Hill, 2005)
Healthy living; Money and consumer issues; Accidents and emergencies; Community; Work; Communication.
Includes index
Keywords: English language -- Study and teching; Tiếng Anh